Analisis financing to deposit ratio (fdr) dan perkembangannya pada bank syariah indonesia tahun 2019-2023: studi literatur - Aqilah, Naurah Nadhifah; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2026)
This article aims to analyze the development of the Financing to Deposit Ratio (FDR) at Bank Syariah Indonesia (BSI) from 2019 to 2023 using a literature study approach. FDR is a key indicator used to evaluate a bank’s liquidity capability through the comparison between total financing disbursed and third-party funds collected. This study synthesizes findings from journals, annual reports, and financial publications over the past five years to identify FDR trends, influencing factors, and its implications for BSI’s liquidity stability. The results indicate that FDR dynamics are affected by financing growth, third-party fund movement, national economic conditions, pandemic impacts, and internal bank policies. Despite fluctuations, BSI’s FDR remains within a stable range in accordance with regulatory standards.